Correlation Between Vitamin D Levels and Hemoglobin Levels in Patients with End-Stage Renal Disease on Maintenance Hemodialysis (Medical Forum Monthly, 2020)
Objective: To study the correlation between Vitamin D levels and hemoglobin levels in patients with End-Stage Renal Disease on maintenance hemodialysis.Study Design: Cross sectional study.Place and Duration of Study: This study was conducted at the Dialysis Unit, Nephrology Department, Shaikh Zayed Hospital Lahore from 18-06-2017 to 17-01-2018.Materials and Methods: This cross sectional study was performed from 18-06-2017 to 17-01-2018. A total of 119patients were selected in Hemodialysis Unit, Shaikh Zayed Hospital Lahore. Participants were selected through non probability consecutive sampling technique. Samples for serum vitamin D and hemoglobin levels were taken immediately before dialysis.Results: The mean age of the patients was 44.42±11.09 years. 49.6% (n=59) of the patients had age 18-44 years, while 50.4% (n=60) of patients had age 50-70 years. Vitamin D levels were positively correlated with hemoglobin levels with Pearson correlation coefficient of 0.728.Conclusion: Vitamin D levels are positively correlated with hemoglobin concentrations in ESRD patients on maintenance hemodialysis.